Empathetic storytelling in reportage photography by Ryszard Kapuściński: image, text, context: Fotografia reportażowa Ryszarda Kapuścińskiego jako opowieść empatyczna: obraz, tekst, kontekst - Wysocka, Aneta (Media - Culture - Social Communication, 2024)
This article contains a semantic and pragmatic analysis of Ryszard Kapuściński’s reportage photographs, published in the first editions of his books and in his original photo albums. The findings of cognitive and cultural linguistics are the methodological basis for the study (Mandler, Taylor, van Dijk and others), which, in significant respects, correspond to theories from other humanities and social sciences, describing the meaning of visual messages (Baudrillard, Bourdieu, Feininger, Goffman, Lundsen, Sonesson and others). The aim of the research is to describe the course and possible results of the process of interpreting photography, which, in Kapuściński’s case, is a multimodal (verbal-visual) message with storytelling potential. An analysis of Kapuściński’s photographs has shown three main factors influencing the interpretation of his verbal-visual works: 1) cultural context dependency, 2) metatextual determination, and 3) intertextual associations. The study has also shown the close relationship between his literary reportages and photography in the illocutionary (intentional) dimension and, more broadly, in the way of understanding the most general duties of a journalist.